2018
DOI: 10.1002/chem.201705049
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Enzymatic Strategies for Bacterial and Mammalian Cell Surface Engineering

Abstract: The cell surface serves important functions such as the regulation of cell-cell and cell-environment interactions. The understanding and manipulation of the cell surface is important for a wide range of fundamental studies of cellular behavior and for biotechnological and medical applications. With the rapid advance of biology, chemistry and materials science, many strategies have been developed for the functionalization of bacterial and mammalian cell surfaces. Here, we review the recent development of chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 113 publications
(178 reference statements)
0
37
0
Order By: Relevance
“…However, dynamic surface glycan recycling and inevitable cell division processes ultimately restrict the timeframe for appreciable surface reactivity. This issue raises concerns about whether long‐term feeding of cells with unnatural sugars can lead to unexpected effects on cell and microtissue development . Moreover, the importance of spacers on the stability of such cell‐networks requires further studies.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…However, dynamic surface glycan recycling and inevitable cell division processes ultimately restrict the timeframe for appreciable surface reactivity. This issue raises concerns about whether long‐term feeding of cells with unnatural sugars can lead to unexpected effects on cell and microtissue development . Moreover, the importance of spacers on the stability of such cell‐networks requires further studies.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…Over the past decade, there is growing interest in the chemical community to develop synthetic tools that can install chemical and biological handles onto different types of cells to replace or assist natural interactions occurring on the cell surface. 7 In the case of mammalian cells, one common approach is to modify pericellular matrix or surface proteins via non-covalent or covalent reactions. 8 Examples include the use of natural functional groups (primary amine, terminal thiol, and carboxyl), 9 metabolic engineering of unnatural amino sugar analogs as reactive tags, 10,11 and insertion of functional motifs with hydrophobic anchors into the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed protein binders based on ODN-small-molecule conjugates [21][22][23] and have shown that such binders can be designed to reversibly interact with different proteins 21,22 and even mediate unnatural protein-protein communication processes 21 . Parallel to these efforts, much progress has been made in the ability to modify cell surfaces with synthetic agents that bear unique functionalities [28][29][30][31] . The synthetic agents can be designed to selectively target and be covalently attached to natural CSPs [32][33][34][35][36] .…”
mentioning
confidence: 99%